Priority Directions for Facilitating Lifelong Learning in Armenia - Gayane Suren Poghosyan (Envigogika)
This study aims to identify the priority areas for implementing lifelong learning in Armenia. A four-stage project-based learning method was applied in the context of the research; a total of 164 respondents participated in the survey and interviews, including educators, high school students, and students from pre-vocational educational institutions across four regions in Armenia. The analysis of responses to the questionnaire revealed the perceived importance of the teacher training, quality standards, programs, and educational materials. Additionally, external factors were considered, such as cooperation at both local and international levels, the need to update the material-technical base and incorporating new technologies, particularly digital ones. A key takeaway from this analysis is the unanimous agreement among participants on the essential need to embrace lifelong learning and to pursue the necessary reforms of the educational system in Armenia.